The effectiveness of information service with quantum learning models using music to improve student learning - Rahmat Wahyudi; Neviyarni Neviyarni; Agus Irianto (RedWhite Press, 2019)
This research is motivated by still found learners who have no motivation to learn. One of the efforts made to improve learners’ motivation is in learning by giving information service. This study aims to examine the effectiveness of information services with quantum learning model using music to improve learners’ motivation is in learning. This research uses quasi experiment, with quasi experiment form is non-equivalent control group design or non-randomized pretest-posttest control group design. The subjects of this study are the learners’of Islamic Senior High School 1 Payakumbuh as a group of experiments and the learners’ of Islamic Senior High School 2 Payakumbuh as a control group. The research instrument used is Likert Scale model, then will be analyzed using Paired Samples t-test and Independent Samples Test with SPSS version 20.00. The result of the research shows that: (1) there is a significant difference of learning motivation of the students in the experimental group before and after being given information service with quantum learning model using music; (2) there is a difference of learning motivation learners’ in control group before and after given information service without a quantum learning model using music, and (3) there is a difference learning motivation learners’ between the experimental group provided with information service with quantum learning model using music and control group given information service without quantum learning model using music.